THE MEANINGS OF CHRISTIAN SACRED IN THE MODERN PAINTING CULTURE - Лазоревич, Ірина (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Серія Філософія, 2019)
The article will try to cover the issues of the transformation of sacred expressions from the common Christian mystery (with an emphasis on painting material). The specificity of the establishment of the sacred as one of the ideological basis is demonstrated not only in the activity of ecclesiastical and religious institutions, but also in the works of contemporary artists, sometimes not directly related to church corporateness. The researcher points out that currently, sacredness is not only a religious phenomenon. Therefore, the issues that are in one way or another related to the sacred, reflect the key realities of the cultural phenomenon. The author takes into account the fact that the transformation of the key canons of art in Christianity is obvious and historically motivated. It is fuelled by the tendencies of the religious functioning in the secular-post-secular environment, as well as processes of informatization and globalization. The article analyzes the works of the leading artists and architects working in the sphere of Christian art and interprets the meanings of their artistic guidelines. Interdisciplinary coordination of Religious Studies, Philosophy of Religion, Cultural Studies, Aesthetics and Social Psychology is implemented in the research.
Keywords: Christianity, religion, culture, sacredness, art, profane, symbol.